1990
DOI: 10.1111/j.1151-2916.1990.tb06480.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of High‐Purity Vitreous B2S3

Abstract: Preparation schemes for high-purity vitreous BzS3 (v-B2S3) with a S:B ratio of 1.478 k 0.032 are described. Preparation schemes reported in the literature are shown by very sensitive FT-IR measurements to yield v-BZS3 with significant oxygen contamination. Through extreme care taken in carbonizing silica reaction tubes and through the use of very high purity starting materials, oxygen contamination of less than 1% has been achieved. The IR spectrum for very pure v-BZS3 contains only two absorption bands. [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 15 publications
0
61
0
Order By: Relevance
“…First, glassy boron sulfide v-B 2 S 3 , was prepared by reacting the elements in a carbon coated and sealed silica tube [5]. Finely powdered v-B 2 S 3 was placed in a carbon crucible and heated to about 500°C in a long vertical silica reactor [6].…”
Section: Methodsmentioning
confidence: 99%
“…First, glassy boron sulfide v-B 2 S 3 , was prepared by reacting the elements in a carbon coated and sealed silica tube [5]. Finely powdered v-B 2 S 3 was placed in a carbon crucible and heated to about 500°C in a long vertical silica reactor [6].…”
Section: Methodsmentioning
confidence: 99%
“…Cho et al [4,15] showed in the binary Li 2 S + B 2 S 3 glasses through chemical analysis that bands of similar intensity in the 1000-1500 cm À1 range constituted less than 1 wt% of the sample and for this were ignored. The addition of LiI to the x ¼ 0:55 Li 2 S sample some narrowing of the peaks occur, but otherwise it does not appear to significantly alter the structural features seen in the IR spectra.…”
Section: Ir Spectra Of the Glassesmentioning
confidence: 98%
“…As a strong glass-forming material, boron trisulfide (B 2 S 3 ) makes an excellent network glass former [1]. Recent interest in thioborate and related chalcogenide glasses is due to their fast ion conducting (FIC) behavior when suitably doped with alkali sulfide (M 2 S) modifier and considered as solid state electrolytes in solid state batteries [2,3].…”
Section: Introductionmentioning
confidence: 99%